Protein–RNA Dynamics in the Central Junction Control 30S Ribosome Assembly. Issue 18 (11th September 2016) - Baker, Kris Ann; Lamichhane, Rajan; Lamichhane, Tek; Rueda, David; Cunningham, Philip R.
Abstract: Interactions between ribosomal proteins (rproteins) and ribosomal RNA (rRNA) facilitate the formation of functional ribosomes. S15 is a central domain primary binding protein that has been shown to trigger a cascade of conformational changes in 16S rRNA, forming the functional structure of the central domain. Previous biochemical and structural studies in vitro have revealed that S15 binds a three-way junction of helices 20, 21, and 22, including nucleotides 652–654 and 752–754. All junction nucleotides except 653 are highly conserved among the Bacteria. To identify functionally important motifs within the junction, we subjected nucleotides 652–654 and 752–754 to saturation mutagenesis and selected and analyzed functional mutants. Only 64 mutants with greater than 10% ribosome function in vivo were isolated. S15 overexpression complemented mutations in the junction loop in each of the partially active mutants, although mutations that produced inactive ribosomes were not complemented by overexpression of S15. Single-molecule Förster or fluorescence resonance energy transfer (smFRET) was used to study the Mg 2 + - and S15-induced conformational dynamics of selected junction mutants. Comparison of the structural dynamics of these mutants with the wild type in the presence and absence of S15 revealed specific sequence and structural motifs in the central junction that are important in ribosome function. Graphical Abstract: Highlights: Study identified sequence, structure, and dynamic requirements of central junction. Cross-junction interactions especially a Watson–Crick base pair of 654:754 are required. Loss of ribosome function is linked to decreased and improper 30S assembly. Central domain folding requires S15, Mg 2 +, and an ability to pivot at junction. Comprehensive results of central junction study can aid new antibiotic development.